Panduan singkat cara pembuatan arang kayu: alternatif pemanfaatan limbah kayu oleh masyarakat - Iskandar, H.; Santoso, K.D. (Center for International Forestry Research, 2005)
This handy Manual book of “Making Charcoal - Alternative to utilization of wood waste by local communities” was summarized from several topics of “Training on Utilization of Wood-waste by Local Communities for wood carving and charcoal”, carried out on 17-27 April 2004 in MRF Seturan Research station. The training, indeed was following activities CIFOR prior study on wood-waste potential from opening ladang (swidden fallows) and logging activities in Malinau District, East Kalimantan. Dissemination information relating to the alternatives utilization of wood-waste to the broader audiences, particularly the local communities, was the main concern to making this manual book. It is expected that as output of dissemination of this books, local peoples will be enriched with more information regarding the utilization of waste for charcoal making, and will bring impact on each of their own community and livelihood. This impact is, in particular, the change from the present traditional shifting cultivation of slash-and-burn to slash-and-char system. The slash-and-char system increases the intensity and productivity of the ladang (swidden fallows). The rate of deforestation is expected to be reduced by the adoption of this system.